2022
DOI: 10.3389/fimmu.2022.864739
|View full text |Cite
|
Sign up to set email alerts
|

Dual Relationship Between Stromal Cells and Immune Cells in the Tumor Microenvironment

Abstract: The tumor microenvironment (TME) plays a critical role in tumorigenesis and is comprised of different components, including tumor cells, stromal cells, and immune cells. Among them, the relationship between each mediator involved in the construction of the TME can be understood by focusing on the secreting or expressing factors from each cells. Therefore, understanding the various interactions between each cellular component of the TME is necessary for precise therapeutic approaches. In carcinoma, stromal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 179 publications
(167 reference statements)
0
28
0
Order By: Relevance
“…Most of stromal elements, if not all, jointly contribute toward forming of an immunosuppressive TME that enables cancer cells to evade surveillance and attack from body’s immune system (Fig. 5 ) [ 244 ].…”
Section: Stromal Elements and The Immune Systemmentioning
confidence: 99%
“…Most of stromal elements, if not all, jointly contribute toward forming of an immunosuppressive TME that enables cancer cells to evade surveillance and attack from body’s immune system (Fig. 5 ) [ 244 ].…”
Section: Stromal Elements and The Immune Systemmentioning
confidence: 99%
“…In addition, we found that stromal cell levels, including endothelial cells and fibroblasts, in high-risk tumors were significantly higher than those in low-risk tumors. Endothelial cells and fibroblasts are important cells that constitute the tumor microenvironment and can promote the occurrence and development of tumors ( Mun et al, 2022 ). The poor prognosis of high-risk tumors may also be related to the increase in these cells in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Te results of univariate and multivariate Cox regression Te TME is highly complex, and the study of TME can help provide new ideas for the treatment of tumors [18]. Stromal cells and immune cells are two important cell members of the TME [19]. Stromal cells have been demonstrated to be closely associated with the growth, metastasis, drug resistance of several cancers [20][21][22], and immune cells, depending on their type, can play an important role in fghting tumors and in promoting tumor progression or immune escape, respectively [23,24].…”
Section: Discussionmentioning
confidence: 99%